The yeast eIF2 kinase Gcn2 facilitates H2O2-mediated feedback inhibition of both protein synthesis and ER oxidative folding during recombinant protein production - Gast, Veronica; Campbell, Kate; Cecilia Picazo Campos; Engqvist, Martin; Siewers, Verena; Molin, Mikael (bioRxiv, 2021)
Abstract Recombinant protein production is a known source of oxidative stress. Knowledge of which ROS are involved or the specific growth phase in which stress occurs however remains lacking. Using modern, hypersensitive genetic H2O2-specific probes, micro-cultivation and continuous measurements in batch culture, we observed H2O2 accumulation during and following the diauxic shift in engineered Saccharomyces cerevisiae, correlating with peak α-amylase production. In agreement with previous studies supporting a role of the translation initiation factor kinase Gcn2 in the response to H2O2, we find Gcn2-dependent phosphorylation of eIF2α to increase alongside translational attenuation in strains engineered to produce large amounts of α-amylase. Gcn2 removal significantly improved α-amylase production in two previously optimized high-producing strains, but not in the wild-type. Gcn2-deficiency furthermore reduced intracellular H2O2 levels and the unfolded protein response whilst expression of antioxidants and the ER disulfide isomerase PDI1 increased. These results suggest protein synthesis and ER oxidative folding to be coupled and subject to feedback inhibition by H2O2. Importance Reactive oxygen species (ROS) accumulate during recombinant protein production both in yeast and Chinese hamster ovary cells, two of the most popular organisms used in the multi-million dollar protein production industry. Here we document increased H2O2 in the cytosol of yeast cells producing α-amylase. Since H2O2 predominantly targets the protein synthesis machinery and activates the translation initiation factor kinase Gcn2, we removed Gcn2, resulting in increased recombinant α-amylase production in two different previously engineered high-producing protein production strains. Removal of this negative feed-back loop thus represents a complementary strategy for improving recombinant protein production efforts currently used in yeast. Gcn2-deficiency also increased the expression of antioxidant genes and the ER-foldase PDI1, suggesting that protein synthesis and ER oxidative folding are linked and feed-back regulated via H2O2. Identification of additional components in this complex regulation may further improve protein production and contribute to the development of novel protein-based therapeutic strategies.